Penyuluhan Pencegahan Stunting Sejak Dini Bersama Mahasiswa KKN-T Universitas Alma Ata Yogyakarta - Azizah, Dewi (Jurnal Atma Inovasia, 2023)
Stunting is one of the nutritional problems as well as a serious threat to children in Indonesia. Currently, the stunting rate in Indonesia is 37.2% or equivalent to 8 million children with suboptimal growth[3]. This is behind our need to hold a stunting counseling program, especially in pringgading hamlet, Guwosari district, Pajangan District, Bantul Regency. The form of counseling is in the form of providing information services by collaborating with local posyandu cadres to convey information to the community to invite the community to carry out public health movements. The hope is that the holding of stunting counseling activities in pringgading hamlet can increase public awareness regarding the importance of child growth and development so that increasingly noticed and increasing, so as to prevent stunting and reduce the percentage of stunting in Indonesia, especially in pringgading hamlet, Guwosari District, Pajangan District, Bantul Regency Keywords: Student, Counseling, Stunting